Mastering identity and access management with Microsoft Azure : empower users by managing and protecting identities and data - Nickel, Jochen (Packt Publishing, 2019)
Start empowering users and protecting corporate data, while managing identities and access with Microsoft Azure in different environments Key Features Understand how to identify and manage business drivers during transitions Explore Microsoft Identity and Access Management as a Service (IDaaS) solution Over 40 playbooks to support your learning process with practical guidelines Book Description Microsoft Azure and its Identity and access management are at the heart of Microsoft's software as service products, including Office 365, Dynamics CRM, and Enterprise Mobility Management. It is crucial to master Microsoft Azure in order to be able to work with the Microsoft Cloud effectively. You'll begin by identifying the benefits of Microsoft Azure in the field of identity and access management. Working through the functionality of identity and access management as a service, you will get a full overview of the Microsoft strategy. Understanding identity synchronization will help you to provide a well-managed identity. Project scenarios and examples will enable you to understand, troubleshoot, and develop on essential authentication protocols and publishing scenarios. Finally, you will acquire a thorough understanding of Microsoft Information protection technologies. What you will learn Apply technical descriptions to your business needs and deployments Manage cloud-only, simple, and complex hybrid environments Apply correct and efficient monitoring and identity protection strategies Design and deploy custom Identity and access management solutions Build a complete identity and access management life cycle Understand authentication and application publishing mechanisms Use and understand the most crucial identity synchronization scenarios Implement a suitable information protection strategy Who this book is for This book is a perfect companion for developers, cyber security specialists, system and security engineers, IT consultants/architects, and system administrators who are looking for perfectly up?to-date hybrid and cloud-only scenarios. You should have some understanding of security solutions, Active Directory, access privileges/rights, and authentication methods. Programming knowledge is not required but can be helpful for using PowerShell or working with APIs to customize your solutions.